Влияние внешнего взаимодействия щелей на коэффициент эллиптичности излучаемого поля - Шубарин, Ю.В.; Яцук, Л.П. (Radiotekhnika)
Влияние внешнего взаимодействия щелей на коэффициент эллиптичности излучаемого поля